Secularism Confronts Islam: By Olivier Roy, trans. George Holoch (New York and Chichester, UK: Columbia University Press, 2007, 128 pages.) (American Journal of Islam and Society, 2009)
This work by a leading French Islamicist is both an analysis of Islam, secularism,and society in Europe, as well as a prescription for its leaders on howto “correct” their wrongheaded policies with regard to their Muslim minoritiesbased on this analysis. This might seem unduly arrogant on OlivierRoy’s part, but his past landmark books do seem to commend the perspicacityof his views on the subject, and most of all, The Failure of Political Islam(Harvard University Press: 1994) and Globalized Islam: The Search for theNew Umma (Hurst: 2004).On one level, Roy is focused on France: how one might begin to mitigatethe polarization of the French elites in the wake of forbidding the veil in publicplaces and the violence of the 2005 riots in the poorest – mostly Muslim– suburbs of Paris. Indeed, the first chapter is devoted to the historical rootsof France’s virulent version of state-enforced secularism (laïcité). But onanother level, this is a work rich in theoretical analysis, widening its insightsto Britain and the United States and their “common law” version of laïcité, aswell as providing a new theory to the sociology of religion.The intensity of the French debate raises important questions. “The campaignof Islamophobia we are witnessing today is involved in the reshapingof the French political and intellectual landscape” (p. 2). How so? The ChristianRight and the Extreme Right’s suspicion of Islam is now shared by a sizableportion of the Left, which has reacted with fear to the French Muslimcommunity’s new and outspoken rhetoric. School girls want to wear the veilout of pride. And this new Islamic discourse has been promoted both by the“bearded Salafist preacher” and the suave intellectual embodied by TariqRamadan ...